Belief Updating and AI Adoption: Experimental Evidence from Firms - Manuel Menkhoff (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Using a large German firm survey, I randomize information on documented AI productivity gains and industry adoption rates and track firms over time. Beliefs about AI's productivity potential rise significantly after the treatments across the prior distribution without reducing uncertainty. These treatment-induced belief shifts map into behavior: in firms where the respondent has high decision authority, AI adoption is more likely one year later. Information about competitor adoption has direct effects on actions: incumbent adopters cut prices, while not-yet adopters revise business expectations upward. Together, the results highlight the role of expectations, strategic considerations, and informational frictions in shaping technology diffusion and its macroeconomic impact.
Keywords: D22; D84; E22; E31; O33; 330; artificial intelligence; technological change; technology adoption; firm expectations; RCT; belief updating; price-setting